PELAKSANAAN SISTEM INFORMASI MANAJEMEN DAERAH DALAM MENJAMIN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH DI KOTA BITUNG PROVINSI SULAWESI UTARA - Utomo, Decky Dwi; Tumija, Tumija; Pangemanan, Andrew (Fakultas Manajemen Pemerintahan, Institut Pemerintahan Dalam Negeri, 2021)
AbstractIMPLEMENTATION OF THE REGIONAL MANAGEMENT INFORMATION SYSTEM IN ENSURING THE ACCOUNTABILITY OF REGIONAL FINANCIAL MANAGEMENT IN BITUNG CITY, NORTH SULAWESI PROVINCEThe development in the current era of globalization has an impact on every aspect of government, especially in the field of information technology that is used by the government to facilitate the implementation of services carried out to minimize existing problems. One of the problems of regional government that has always been an obstacle in making reports on the implementation of regional government is Regional Financial Management. This study aims to describe the implementation of the Regional Management Information System in ensuring the Accountability of Regional Financial Management in Bitung City which is based on Law Number 23 Year 2014 Article 293 and Article 330 concerning Regional Government giving the Mandate to Regulate Regional Financial Management. The research method used is qualitative research with descriptive methods with an inductive approach. Data collection techniques using observation, interviews, documentation. The interview used by the writer in this research is structured interview, using purposive sampling. The results of this study found that there is still a lack of training provided to SIMDA Finance management officers at the Regional Financial and Asset Agency, inadequate internet networks, and the absence of local regulations that specifically regulate information systems for the Implementation of Financial SIMDA in regional municipalities. Bitung.Keywords: Implementation, Information Systems, Accountability, Management AbstrakPerkembangan di era globalisasi saat ini memberikan dampak pada setiap aspek pemerintahan khususnya bidang teknologi informasi yang digunakan pemerintah untuk mempermudah pelaksanaan pelayanan yang dilakukan untuk meminimalisasikan permasalahan yang ada. Permasalahan pemerintahan Daerah yang selalu menjadi kendala dalam pembuatan laporan penyelenggaraan pemerintahan daerah salah satunya adalah Pengelolaan Keuangan Daerah. Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan Sistem Informasi Manajemen Daerah dalam menjamin Akuntabilitas Pengelolaan Keuangan Daerah di Kota Bitung yang berdasarkan pada Undang-Undang Nomor 23 Tahun 2014 Pasal 293 dan Pasal 330 tentang Pemerintahan Daerah memberi Amanat Untuk Mengatur tentang Pengelolaan Keuangan Daerah. Metode penelitian yang digunakan adalah penelitian kualitatif dengan metode deskriptif dengan pendekatan induktif. Teknik pengumpulan data dengan menggunakan Observasi, wawancara, Dokumentasi. Wawancara yang digunakan dalam penelitian ini adalah wawancara terstruktur, dengan menggunakan purposive sampling. Hasil dari penelitian ini didapati bahwa Masih minimnya pelatihan yang diberikan kepada para petugas pengelola SIMDA Keuangan di Badan Keuangan dan Aset Daerah, Jaringan internet yang belum memadai, serta belum adanya peraturan daerah yang mengatur secara khusus mengenai sistem informasi Pelaksanaan SIMDA Keuangan di wilayah pemerintah daerah Kota Bitung.Kata Kunci: Pelaksanaan, Sistem Informasi, Akuntabilitas, Manajemen